Accessing personal medical records online: A means to what ends?. Issue 2 (February 2015) - Shah, Syed Ghulam Sarwar; Fitton, Richard; Hannan, Amir; Fisher, Brian; Young, Terry; Barnett, Julie
Highlights Patients use EHRs for personal health management. Patients trust the information provided in EHRs. Accessing EHRs creates a new set of expectations among patients.